Cervical pessary use and preterm labor prevention - Jácome, Amanda (2020)
Introduction: Preterm delivery is an important cause of perinatal morbidity and mortality with global social and economic repercussions. Timely intervention in the identification of risk factors and proper management reduce their incidence and avoid the consequences of prematurity.Objective:This work is carried out with the aim of highlight the cervical pessary as a mechanical tool in the prevention of preterm birth and a treatment option in pregnancies over 25 weeks with cervical insufficiency.Case presentation: This is a 38-year-old patient with a history of spontaneous preterm delivery (33 weeks), who was admitted at 21 weeks of pregnancy with cervical dilation of 3cm and shortening of the cervical length of 14mm, ultrasound signs: sludge and funneling. Expectant management was opted, with complementary measures: administration of antibiotics, progesterone and use of a cervical pessary. After clinical control of the infection and greater cervical shortening to 7mm despite the use of progesterone, a cervical pessary was placed at 25.5 weeks, at 27.5 weeks she was discharged, at 36.6 weeks she was discharged. The pessary was removed after the start of uterine activity.Discussion: Progesterone and cerclage are the measures of choice in cases of cervical insufficiency, however, given the technical difficulties of placement; the pessary represented an alternative.Conclusion: The use of the pessary allowed the pregnancy to progress to term with beneficial results and without evidence of adverse effects.